(untitled) (Journal of Dhaka National Medical College & Hospital, 2013)
The Ilizarov External Fixator is the name of a device that is used to treat fracture & stabilize fracture and may also be used to lengthen bone & correct deformity. In 1950, G.A Ilizarov introduced not only a new apparatus but even more importantly a new understanding of the biology of lengthening. This technique enables correction of angular, rotational & translational osseous deformities as well as rotation of limb length equality. The Ilizarov technique is applied to any parts of the body. This technique has a high rate of success in achieving union & eradicating infection, bone loss and mal-alignment. It has produced excellent results where tradition methods have failed to achieve optimum result. A 50yrs old man was admitted at Dhaka National Medical Institute Hospital with a badly comminuted open fracture at the lower part of Tibia & Fibula. It was very unstable. The patient was treated by using Elizarov External Fixator. Angulation & rotation was corrected repeatedly and ultimately resulted with nice union at the end of 7 month J.Dhaka National Med. Coll. Hos. 2013; 19 (02): 49-51